Smoothed Particle Hydrodynamics and Model-Order Reduction for Efficient Modeling of Fluid-Structure Interaction. Issue 1 (2015) - Schörgenhumer, Markus; Humer, Alexander; Gerstmayr, Johannes
Abstract: Modeling the interaction of fluids with moving, flexible structures is a major and still very challenging subject in the field of multi-physics problems. In this work, an efficient computational approach based on the coupling of modally reduced flexible multibody systems with fluids modeled by means of smoothed particle hydrodynamics is outlined.